2015
DOI: 10.1523/jneurosci.1391-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Brain Region-Specific Trafficking of the Dopamine Transporter

Abstract: The dopamine (DA) transporter (DAT) controls dopaminergic neurotransmission by removing extracellular DA. Although DA reuptake is proposed to be regulated by DAT traffic to and from the cell surface, the membrane trafficking system involved in the endocytic cycling of DAT in the intact mammalian brain has not been characterized. Hence, we performed immunolabeling and quantitative analysis of the subcellular and regional distribution of DAT using the transgenic knock-in mouse expressing hemagglutinin (HA) epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(117 citation statements)
references
References 55 publications
8
98
2
Order By: Relevance
“…We and others have shown that the closely related SLC6 transporters DAT and SERT, like NET, undergo considerable constitutive internalization (18,20,22,23), although a recent study has indicated that DAT only might undergo modest endocytic trafficking in vivo (63). Nonetheless, according to our previous findings and in contrast to NET, DAT and SERT are mainly sorted to late endosomes and lysosomes, and, if recycled, they are more likely to follow the Rab4 short loop recycling pathway (22,24).…”
Section: Discussionsupporting
confidence: 50%
“…We and others have shown that the closely related SLC6 transporters DAT and SERT, like NET, undergo considerable constitutive internalization (18,20,22,23), although a recent study has indicated that DAT only might undergo modest endocytic trafficking in vivo (63). Nonetheless, according to our previous findings and in contrast to NET, DAT and SERT are mainly sorted to late endosomes and lysosomes, and, if recycled, they are more likely to follow the Rab4 short loop recycling pathway (22,24).…”
Section: Discussionsupporting
confidence: 50%
“…Gene silencing studies suggest that both constitutive and PKC-stimulated DAT internalization in nonneuronal cell lines is clathrindependent (37); however, whether chronic clathrin depletion artifactually skews these studies is uncertain. A recent study examining DAT trafficking in a knock-in mouse encoding a DAT extracellular epitope tag observed only modest DAT endocytosis and little/no clathrin colocalization under basal conditions (38). However, it is unclear whether antibody-bound DAT traffics similar to native DAT, as we investigate here.…”
Section: Discussionmentioning
confidence: 78%
“…; Block et al . ), and thus, functional changes in DAT may be a major contributor to L‐DOPA‐associated kinetic changes in DA clearance. By contrast, other in vivo studies demonstrate that acute high doses of L‐DOPA significantly decrease striatal DAT binding in rodents, suggesting that L‐DOPA induces DAT internalization (Scheffel et al .…”
Section: Discussionmentioning
confidence: 99%